Basic Sciences: An Alternative career? (Kathmandu University Medical Journal, 2014)
Career selection is a crucial and a complex process which is also true in the medical profession as well. In the context of our country, due to the limited opportunity and proper guidance, migration of medical graduates to foreign countries is increasing. Though, clinical subjects have a huge attraction, basic science field has failed to impress our medical graduates. In current scenario, basic science field seems to be a dumping site for the incompetent as the candidates who have failed trying their luck elsewhere stumble upon basic science careers though it is not true for all. Moreover, a very few medical graduates are interested in developing their career as a basic scientist. Therefore, to motivate today’s young medical graduates, there is a need of a good mentor along with a proper career guidance which can help them to understand the basic science field as an alternative career. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11033 Kathmandu University Medical Journal Vol.11(1) 2013: 78-80